Improving Efl Students' Cohesion and Coherence Through Simple View of Writing - Diraja Zamach Syarif; Nora Fitria; Cut Faizah; Faudi Faudi (Syntax Literate, 2023)
Mastery of English as a foreign language (EFL) is an important skill in today's globalized world. One important aspect of language acquisition is good writing skills. However, students learning English as a foreign language often need help developing cohesion and coherence in writing. This study aims to examine whether a simple view of writing can improve EFL students' cohesion and coherence. This study utilized a quantitative method. Data were collected using two instruments: cohesion and coherence tests and student response questionnaires. The data were analyzed using descriptive statistical analysis and regression tests. The results showed that a simple view of writing can improve EFL students' cohesion and coherence. Students who used a simple view of writing learning had higher cohesion and coherence scores than students who did not use a simple view of writing learning. English teachers can use this technique to help students write more coherence and cohesive texts.